Attention and the crossmodal construction of space. - Driver, J; Spence, C (1998)
Traditional studies of spatial attention consider only a single sensory modality at a time (e.g. just vision, or just audition). In daily life, however, our spatial attention often has to be coordinated across several modalities. This is a non-trivial problem, given that each modality initially codes space in entirely different ways. In the last five years, there has been a spate of studies on crossmodal attention. These have demonstrated numerous crossmodal links in spatial attention, such that attending to a particular location in one modality tends to produce corresponding shifts of attention in other modalities. The spatial coordinates of these crossmodal links illustrate that the internal representation of external space depends on extensive crossmodal integration. Recent neuroscience studies are discussed that suggest possible brain mechanisms for the crossmodal links in spatial attention.